Where Does Salvation Come From? A Reading of 2 Kings 5:1–27 - Ska, Jean Louis (The Biblical Annals, 2023)
2 Kings 5:1–27 describes the healing of a foreigner, Naaman the Syrian, a high officer of the King of Damascus, by Elisha, a prophet in Israel. Naaman the Syrian suffers from a kind of skin disease called “leprosy” in the Bible. He thinks that, being rich and powerful, he is in possession of the means to get healed. He has to change his mind and his behaviour, though. He is healed when he agrees to listen to an Israelian maidservant, a slave, to the prophet Elisha, and to his own servants. When he bathes in the Jordan, he symbolically enters the Promised Land because he is healed and, at the same time, he acknowledges that Yhwh is the only Lord of the universe.